2023
DOI: 10.20409/berj.2023.413
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Challenges to Adoption of Drones in the Logistics Sector Using the Best-Worst Method

Abstract: Drones, which are unmanned aerial vehicles, are used in various areas. Some important worldwide companies have been interested to integrate drone technology into their logistics applications. Although the use of drones promises various advantages such as reducing costs and improving responsiveness in the logistics sector, there are also various challenges to the adoption of this technology. Therefore, this study aims to identify and prioritize the challenges to drone technology adoption in the logistics sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(111 reference statements)
0
0
0
Order By: Relevance
“…parachute [16] Figure 4. : Drone delivery using cable [17] An example of drone usage in l The usage of drones in logistics can also be demonstrated using the example of the maritime industry.…”
Section: Figure 3: Drone Delivery Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…parachute [16] Figure 4. : Drone delivery using cable [17] An example of drone usage in l The usage of drones in logistics can also be demonstrated using the example of the maritime industry.…”
Section: Figure 3: Drone Delivery Usingmentioning
confidence: 99%
“…According to Sah, B. et al [15], the regulations, and threat to privacy and security, public perception, environmental issues, technical aspects, and economic aspects are one of the main challenges for the implementation of drones in logistics sector. Çıkmak et al [16] have also concluded that the largest challenges are the regulatory issues, followed by security and safety.…”
Section: Challenges Of Drone Use In Logisticsmentioning
confidence: 99%